MORPHOLOGY AND DISTRIBUTION OF Α-NAPHTHYL BUTIRATE ESTERASE AND NAPHTHOL AS-D CHLOROACETATE ESTERASE IN NORMAL MYELOMONOCYTIC PRECURSORS STUDIED BY THE CELL MICROARRAY - O. S. Fedyanina; A. O. Zakirova; A. E. Zadorozhnaya; N. M. Kapranov; A. N. Khvastunova; P. A. Yadgarova; А. V. Filatov; O. S. Burova; F. I. Ataullakhanov; S. А. Kuznetsova (Онкогематология)
Here we describe and qualitatively characterize the distribution of mononuclear cells isolated from bone marrow aspirate of healthy donors and sorted by their surface CD antigens on a cell microarray by morphology (for 11 donors) and by absence or presence of α-naphthyl butyrate esterase and naphthol AS-D chloroacetate esterase (for 9 donors). These data can be used as a reference for the diagnosis of acute myeloid leukemia using the cell microarray.